APBN 2020: analisis kinerja pendapatan negara selama pandemi Covid-19 - Muhammad Hamdan Sayadi (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2021)
The Government has reduced the State Revenue and Expenditure Budget of 2020 twice through Presidential Regulation No 54 and 72 of 2020 replacing Act No 20 of 2019 about the State Revenue and Expenditure Budget. The amount of the decline of state revenue budget through the presidential regulation is Rp533,25 trillion. The decline of state revenue budget twice shows an indication of the decline of state revenue performance of 2020 because of the Covid-19 pandemic. This paper aims to analyze the performance of country income of the Republic of Indonesia during the Covid-19 pandemic in 2020. This paper used descriptive statistics as a data analysis technique based on the variance analysis of income budget and analysis of income growth. The results showed that the performance of state income during the Covid-19 pandemic in 2020 decreased quite significantly from the same period in 2019. Income budget realization in 2020 decreased by 16,53 percent or Rp323,61 trillion from the same period in 2019. If the income budget realization is observed in detail, the realization of tax revenue decreased by 19,67 percent and non-tax revenue decreased by 16,42 percent.